Determinants of Rural Women’s Accessibility to Primary Health Care Services in Iseyin Local Government Area, Oyo State - Adeniyi, Rhoda Titilayo; Olayemi , Adebayo Oyefunke; Jegede, C. O. (Journal of Science, Technology and Innovation Research, 2025)
The study assessed the determinants of rural women's accessibility to Primary Health Care services in Iseyin Local Government Area of Oyo State, Nigeria. A multistage sampling procedure was used to select 120 respondents. Data on respondents' socioeconomic characteristics, health challenges, and access to primary healthcare services and constraints to Primary Health Care services were collected using an interview schedule and analyzed using percentages, frequency, mean, weighted mean score, Pearson Moment Correlation, and Chi-square at α0.05. The results revealed that the respondents' mean age, monthly expenditure on health, and years of livelihood experience were 41.0 years, ₦5,215.5 and 7.03 years respectively; with monogamy marriage pattern (77.5%), and livelihood activities being farming (96.6%). The most common health challenges experienced by rural women were malaria (WMS=1.93), stomach upset (WMS=1.88), and arthritis (WMS=1.82). Also, immunization against diseases (WMS=3.02), antenatal care (WMS=2.87), and postnatal care (WMS=2.46) were the most accessible primary health care services by the respondents, and was high for 53.3 %. In contrast, high cost of drug (WMS=1.03), inadequate health facilities (WMS=0.98), and unexpected charges (WMS=0.95) were the constraints to access the primary health care services by the respondents. The determinants of respondents’ access to Primary Health Care services were age (r=0.250), years of education (r=0.246), household size (r=0.221), years of livelihood experience (r=0.243), constraints index (r=-0.256), and health challenges index (r=0.264). The determinants of respondents' access to the PHC services were their personal characteristics and the health challenges encountered.